2015
DOI: 10.1016/j.neuroimage.2015.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Causal interpretation rules for encoding and decoding models in neuroimaging

Abstract: Causal terminology is often introduced in the interpretation of encoding and decoding models trained on neuroimaging data. In this article, we investigate which causal statements are warranted and which ones are not supported by empirical evidence. We argue that the distinction between encoding and decoding models is not sufficient for this purpose: relevant features in encoding and decoding models carry a different meaning in stimulus-and in response-based experimental paradigms. We show that only encoding mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 38 publications
1
107
1
Order By: Relevance
“…As the multivariate fNIRS regression model linearly combines multiple channels to predict current working memory load, one approach would be to interpret the weights of these decoding models. However, decoding model weights are hard to interpret for various reasons (Reichert et al, 2014; Weichwald et al, 2015). Therefore, we performed a univariate regression analyses separately for each channel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the multivariate fNIRS regression model linearly combines multiple channels to predict current working memory load, one approach would be to interpret the weights of these decoding models. However, decoding model weights are hard to interpret for various reasons (Reichert et al, 2014; Weichwald et al, 2015). Therefore, we performed a univariate regression analyses separately for each channel.…”
Section: Resultsmentioning
confidence: 99%
“…Because weights of regularized multivariate decoding models can be hard to interpret (Reichert et al, 2014; Weichwald et al, 2015), we used univariate linear regression to determine for each channel separately if it can predict the current working memory load level. These analyses revealed multiple predictive brain areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies with frontal lesion patients demonstrated that complex cognitive control processes involve rostral frontal regions and less complex cognitive control processes engage caudal frontal regions Azuar et al, 2014). From a broader perspective, the level of inference of lesion (Rorden and Karnath, 2004) and TMS (Dayan et al, 2013) studies is generally higher than the level of inference of functional magnetic resonance imaging (fMRI) studies (Poldrack, 2011;Weichwald et al, 2015). Thus, previous frontal lesion studies together with present TMS findings suggest that complex cognitive control functions are represented in rostral lateral frontal cortex.…”
Section: Discussionmentioning
confidence: 44%
“…Currently, brain decoding is the gold standard in multivariate analysis for functional magnetic resonance imaging (fMRI) (Haxby et al, 2001; Cox and Savoy, 2003; Mitchell et al, 2004; Norman et al, 2006) and magnetoencephalogram/electroencephalogram (MEEG) studies (Parra et al, 2003; Rieger et al, 2008; Carroll et al, 2009; Chan et al, 2011; Huttunen et al, 2013; Vidaurre et al, 2013; Abadi et al, 2015). It has been shown that brain decoding can be used in combination with brain encoding (Naselaris et al, 2011) to infer the causal relationship between stimuli and responses (Weichwald et al, 2015). …”
Section: Introductionmentioning
confidence: 99%